2010
DOI: 10.4028/www.scientific.net/msf.645-648.1057
|View full text |Cite
|
Sign up to set email alerts
|

Operation of Silicon Carbide BJTs Free from Bipolar Degradation

Abstract: The mechanisms of bipolar degradation in silicon carbide BJTs are investigated and identified. Bipolar degradation occurs as result of stacking fault (SF) growth within the low-doped collector region. A stacking fault blocks vertical current transport through the collector, driving the defective region into saturation. This results in considerable drop of emitter current gain if the BJT is run at a reasonably low collector-emitter bias. The base region does not play any significant role in bipolar degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…The higher junction temperatures resulting from operating the SJT at either a higher base-plate temperature or a higher duty cycle/lower frequency increases the capturing efficiency of these traps, which results in a greater current gain compression. The absence of a quasi-saturation region in the output characteristics after the long-term operation also suggest that the positive V F shift observed after the long-term operation is associated with the reduced emitter injection efficiency of the GateSource p-n junction, and is not due to the presence of basal plane dislocations in the lightly doped n-drift layer, as observed by Konstantinov et al [3].…”
Section: Long-term Open-drain Operationsupporting
confidence: 61%
See 2 more Smart Citations
“…The higher junction temperatures resulting from operating the SJT at either a higher base-plate temperature or a higher duty cycle/lower frequency increases the capturing efficiency of these traps, which results in a greater current gain compression. The absence of a quasi-saturation region in the output characteristics after the long-term operation also suggest that the positive V F shift observed after the long-term operation is associated with the reduced emitter injection efficiency of the GateSource p-n junction, and is not due to the presence of basal plane dislocations in the lightly doped n-drift layer, as observed by Konstantinov et al [3].…”
Section: Long-term Open-drain Operationsupporting
confidence: 61%
“…On the other hand, the 5.8 hour DC test at a base-plate temperature of 125 °C resulted in a finite increase of the V F by 300 mV at a Drain current of 5 A. However, no quasisaturation region was detected in the output characteristics, as observed in [3] DC versus pulsed current long-term operation: It was reported in [6] that the same charge passing through a SiC PiN diode as a DC or pulsed current causes fundamentally different V F shifts, with the pulsed current causing smaller V F shifts than the DC current. In this work, selected SiC SJTs were subjected to long-duration, 5 A DC or pulsed currents, applied with a pulse width of 30 µs, and at a switching frequency of 14.3 kHz and at a case temperature of 125 °C.…”
Section: Influence Of Base-plate Temperaturementioning
confidence: 76%
See 1 more Smart Citation
“…7(b) and (c)]. According to Konstantinov et al [3], the absence of a quasi-saturation region in the post-test characteristics indicates that the observed V F increase is not due to carrier trapping by BPDs in the lightly doped n-drift layer.…”
Section: ) Influence Of Base-plate Temperaturementioning
confidence: 80%
“…A simulation-focused study [2] attributed the cause for the observed current gain compression in SiC BJTs to electrical carrier traps in the base-emitter space charge region or in the bulk of the quasi-neutral base layer. Another study [3] ascribed the current gain compression to basal plane dislocations (BPDs) in the base and/or collector regions. Ghandi et al reported [4] significant current gain degradation for 3-mm 2 SiC BJTs but nearly stable β for smaller Manuscript area (0.04 mm 2 ) devices, when the devices were subjected to long-term operation.…”
Section: Introductionmentioning
confidence: 99%